HERPETOFAUNA PADA HABITAT HUTAN BATU GAMPING DI MANOKWARI, PAPUA BARAT; SPESIES, KERAGAMAN, KEKAYAAN DAN POPULASI - Dwi Nurhayat; Deny Anjelus Iyai; Desni Saragih; Yubelince Runtuboi; Hendrik Burwos; Isti Widayati; Stepanus Pakage; Hengky Wambrauw (Jurnal Biosilampari : Jurnal Biologi, 2020)
The research was conducted in the Maruni limestone forest habitat. The observation plots were carried out at an altitude of 35 masl to> 212 masl. Observations were made 2 times every day (day and night). The method of calculating diversity is done using the Shannon-Wieners Index and the species population is calculated using the Alikodra formula. 11 species were found that belong to the Varanidae, Boidae, Gekkonidae, Ranidae, and Hylidae families. The diversity of wildlife in the Maruni limestone location follows the altitude of the habitat. Reptiles do not differ according to height. The most common types are in the class of lizards, monitor lizards, and frogs. The types of herpetofauna that can be found are carnivores and are not protected. This type of monitor lizard can be found in abundance in low areas to an altitude of> 200 meters above sea level. Meanwhile, monitor lizards can be found in wet forests and near water sources. Similar to lizards, frogs inhabit wet or watery areas. The diversity of wildlife species in limestone habitats in each class of Reptiles is 18%. The population of herpetofauna species found varied between 25-1200 individuals.